Twisted electromagnetic sinc Schell-model beam and its transmission in a turbulent atmosphere - Zhang, Changyou; Fu, Wenyu (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
We present the twisted electromagnetic sinc-correlation Schell-model (EM TSSM) beam as an extension of the cylindrical sinc Schell-model beam and analyze the necessary source parameter conditions to generate a physically viable beam. Furthermore, we thoroughly investigate the propagation properties of the EM TSSM beam in atmospheric turbulence using the extended Huygens–Fresnel integral, explicitly focusing on spectral intensity, degree of polarization (DOP), and degree of coherence (DOC). It shows that the twisted phase has a noticeable impact on the intensity profiles of these beams, causing them to exhibit rotation and self-splitting while still maintaining their shape in free space. Moreover, during propagation through a turbulent atmosphere, it exhibits self-combining properties over a long range and recovers the plat-topped distribution. Compared with the sinc Schell-model beam without the twisted phase, the DOP distribution of such a beam can rotate around its distribution center. As these beams propagate through turbulent atmospheres, they can self-heal their DOP distribution within specific ranges affected by atmospheric turbulence. A twist factor causes non-unidirectional rotation of the DOC distribution in free space. The DOC gradually transforms from multi-strip profiles into a Gaussian-like distribution. Furthermore, the beam parameters play a crucial role in shaping the DOC. The results will be useful in optical trapping and optical communication.
Optica Applicata, Vol. 54, 2024, nr 1, s. 15-29
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; twisted; sinc Schell-model beam; beam propagation; atmospheric turbulence